Naturalisme pas mort : Lettres inédites de Paul Alexis à Emile Zola, 1871-1900 - Bakker, B. H. (Book collections on Project MUSE., 1971)
Paul Alexis was a novelist, journalist, and dramatist, one of the€ naturalistes, and a friend of Emile Zola. This volume brings together for the first time the 229 letters still in existence from him to Zola.